2017
DOI: 10.1093/jisesa/iex071
|View full text |Cite
|
Sign up to set email alerts
|

Localization of an Aldo-Keto Reductase (AKR2E4) in the Silkworm Bombyx mori (Lepidoptera: Bombycidae)

Abstract: The aldo-keto reductase AKR2E4 reduces 3-dehydroecdysone to ecdysone in the silkworm Bombyx mori L. In this study, a quantitative polymerase chain reaction analysis revealed that the level of AKR2E4 mRNA was higher in the testes than in other tissues, and a western immunoblot analysis revealed that the AKR2E4 content in the testes was stage-specific from the fifth larval instar to the pupal stage. Immunohistochemical analysis showed that the AKR2E4 protein was present in cyst cells associated with sperm cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In vitro experiments, performed from the testes of several moth species including A. ipsilon, have highlighted that this organ is able spontaneously to produce a variety of ecdysteroids and in particular 20E which is known to initiate the spermatogenesis [41,51]. In line with this finding, a recent immunological study has unveiled the presence of ecdysteroidogenic enzymes within the testicular sperm cells and spermatocytes in the moth B. mori [52]. Considering all the above data, AiHR38 could play a role in regulating testicular activity in A. ipsilon males, probably by interfering on the ecdysteroidogenesis, similar to the action of its NR4A1 homologue.…”
Section: Discussionmentioning
confidence: 81%
“…In vitro experiments, performed from the testes of several moth species including A. ipsilon, have highlighted that this organ is able spontaneously to produce a variety of ecdysteroids and in particular 20E which is known to initiate the spermatogenesis [41,51]. In line with this finding, a recent immunological study has unveiled the presence of ecdysteroidogenic enzymes within the testicular sperm cells and spermatocytes in the moth B. mori [52]. Considering all the above data, AiHR38 could play a role in regulating testicular activity in A. ipsilon males, probably by interfering on the ecdysteroidogenesis, similar to the action of its NR4A1 homologue.…”
Section: Discussionmentioning
confidence: 81%
“…We also observed that myrosinase 1 and arylsulfatase B were upregulated after both sugar‐mimic alkaloid treatments (Figure 4b). Moreover, Aldo‐Keto Reductase (AKR2E4), plays an important role in 3‐dehydroecdysone conversion to ecdysone and spermatogenesis in silkworm testes (Yamamoto, Ozakiya, & Uno, 2017). AKR2E4 was also upregulated after both types of sugar‐mimic alkaloid treatments.…”
Section: Resultsmentioning
confidence: 99%
“…Increased ability to metabolize specific steroids during testicular development, such as increased expression of Aldo-keto reductase family 1 member C3, the same family member as Aldo-keto reductase family 1 member A1, during testicular development in domestic cats 32 . The level of Aldo-Keto Reductase mRNA in silkworm testis is higher than that in other tissues, which plays an important role in the spermatogenesis of silkworm 33 . Pachytene checkpoint protein 2 homolog was searched by Uniprot database.…”
Section: Differential Proteinmentioning
confidence: 89%